Cannabis practices among a gender-diverse sample of young adults - Cara A. Struble; Jacob T. Borodovsky; Mohammad I. Habib; Deborah S. Hasin; Dvora Shmulewitz; Ofir Livne; Claire Walsh; Efrat Aharonovich; Alan J. Budney (Drug and Alcohol Dependence Reports, 2022)
Background: Gender is an important factor in understanding cannabis patterns, yet few studies have explored cannabis patterns among gender minority (GM) individuals – particularly among high-risk age groups including young adults. The evolving cannabis market is reshaping typical patterns of cannabis use in the U.S. The combination of these factors warrants increased efforts to examine cannabis practices in gender-diverse samples. Methods: Online survey participants between 18 and 34 (N = 2377) from the U.S. provided information on cannabis practices from May – July 2021. Gender differences across several cannabis outcomes (onset, methods of consumption, product potency, frequency, and quantity) were assessed. Bivariate tests and multiple regression models examined associations between gender (cisgender men: n = 1020; cisgender women: n = 1178; and GM: n = 179) and cannabis outcomes adjusting for sociodemographic characteristics. Results: In regression models adjusted for sociodemographic characteristics, GM identity was associated with later age of onset and lower likelihood of daily use compared to cisgender men and women. Identifying as a GM person or cisgender woman was associated with fewer lifetime methods of consumption and less potent plant and concentrate product usage. Conclusions: Findings provide initial insights into potential gender differences in cannabis practices from a sample of heavy cannabis users. GM young adults report use patterns indicative of lower risk compared to cisgender men and women in our sample. Future investigations of gender differences in cannabis use that explore specific gender minority categories and that include alternative sampling strategies are needed to better understand differential risks associated with gender.